A Sequentially Copper-Catalyzed Alkyne Carboxylation–Propargylation–Azide Cycloaddition (CuACPAC) Synthesis of 1,2,3-Triazolylmethyl Arylpropiolates - Schreiner, Ella; Wilcke, Tobias; Müller, Thomas J. J. (Synlett, 2016)
Concatenation of copper-catalyzed alkyne carboxylation–alkylation and copper-catalyzed alkyne–azide cycloaddition gives a novel sequentially copper-catalyzed alkyne carboxylation–propargylation–azide cycloaddition (CuACPAC) process furnishing 1,2,3-triazolylmethyl arylpropiolates via a consecutive four-component synthesis. The CuACPAC can be expanded to a five-component synthesis of 1,2,3-triazolylmethyl 3-amino arylacrylates by a concluding Michael addition in the same pot.
Keywords: alkynes; azides; carboxylation; catalysis; cycloaddition; multicomponent reaction